2022
DOI: 10.21203/rs.3.rs-1984500/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Microbial eco-evolutionary responses amplify global soil carbon loss with climate warming

Abstract: Soil microbes respond to warming climates through variation in traits linked to the decomposition of soil organic matter, which impacts global soil carbon emissions. Microbial trait variation is shaped by eco-evolutionary processes; yet soil carbon models largely ignore such processes and their implications for global responses to warming. Here, we apply eco-evolutionary theory to a microbe-enzyme model to optimize a key microbial trait controlling decomposition and re-calculate soil carbon projections. Eco-ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…By incorporating competition for resources (e.g., carbon and nutrients; space) between evolved and ancestral strains, this method captures some of the complex dynamics of ecological and evolutionary processes occurring within microbial communities. For instance, Abs et al (2022) applied adaptive dynamics to predict the eco-evolutionary dynamics of microbial communities in response to global warming, specifically focusing on allocation to enzyme production as a trait (Figure 4). Their findings revealed that warming reduces the likelihood of cheating for soluble resources, leading to a higher investment in enzyme production.…”
Section: Adaptive Dynamicsmentioning
confidence: 99%
See 2 more Smart Citations
“…By incorporating competition for resources (e.g., carbon and nutrients; space) between evolved and ancestral strains, this method captures some of the complex dynamics of ecological and evolutionary processes occurring within microbial communities. For instance, Abs et al (2022) applied adaptive dynamics to predict the eco-evolutionary dynamics of microbial communities in response to global warming, specifically focusing on allocation to enzyme production as a trait (Figure 4). Their findings revealed that warming reduces the likelihood of cheating for soluble resources, leading to a higher investment in enzyme production.…”
Section: Adaptive Dynamicsmentioning
confidence: 99%
“…For instance, Abs et al. (2022) applied adaptive dynamics to predict the eco‐evolutionary dynamics of microbial communities in response to global warming, specifically focusing on allocation to enzyme production as a trait (Figure 4). Their findings revealed that warming reduces the likelihood of cheating for soluble resources, leading to a higher investment in enzyme production.…”
Section: Roadmap To Integrate Microbial Evolution In Biogeochemical M...mentioning
confidence: 99%
See 1 more Smart Citation
“…More mechanistic modelling approaches are starting to emerge. Abs et al proposed a mathematical method based on game theory to predict the microbial community eco-evolutionary response to warming (Abs et al, 2022). This method accounts for progressive community trait change modifying the ecological environment (resources, competition), which initiates an eco-evolutionary feedback to modify selection of community traits.…”
Section: How Should We Model Microbial Eco-evolutionary Mechanisms In...mentioning
confidence: 99%
“…Given that environmental selection varies between locations and over time, microbial parameters should reflect spatiotemporal variation. An early attempt to integrate spatio‐temporal variation in microbial composition demonstrated that projections of C loss by 2100 nearly doubled (Abs et al, 2022), highlighting the need to better understand what environmental factors determine microbial properties, especially within a community context.…”
Section: Question: Do Microbes Matter For Soil Biogeochemical Cycling?mentioning
confidence: 99%